2011
DOI: 10.1111/j.1365-2443.2011.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of target genes for the CDK subunits of the Mediator complex

Abstract: Mediator is a large complex containing up to 30 subunits that consist of four modules each: head, middle, tail and CDK/Cyclin. Recent studies have shown that CDK8, a subunit of the CDK/Cyclin module, is one of the key subunits of Mediator that mediates its pivotal roles in transcriptional regulation. In addition to CDK8, CDK19 was identified in human Mediator with a great deal of similarity to CDK8 but was conserved only in vertebrates. Previously, we reported that human CDK19 could form the Mediator complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 26 publications
1
47
0
1
Order By: Relevance
“…In previous studies, we demonstrated that CDK19 forms a CDK8-independent Mediator complex (25). Furthermore, we observed that CDK19 is expressed in a tissue-specific manner, whereas CDK8 is ubiquitously expressed (26). DNA microarray analysis of the target genes of each CDK complex revealed extensive overlap in their target gene preferences (26).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…In previous studies, we demonstrated that CDK19 forms a CDK8-independent Mediator complex (25). Furthermore, we observed that CDK19 is expressed in a tissue-specific manner, whereas CDK8 is ubiquitously expressed (26). DNA microarray analysis of the target genes of each CDK complex revealed extensive overlap in their target gene preferences (26).…”
mentioning
confidence: 74%
“…1, C and D). In these studies, we detected both CDK8 and CDK19 proteins with an anti-CDK8 antibody because this antibody cross-reacts with CDK19 in addition to CDK8 (26); therefore, the ChIP signals from this antibody are designated as CDK8/19 hereafter. Consistent with previous reports (35), PMA treatment facilitated C/EBP␤ recruitment to the promoter regions of its target genes and triggered Pol II transcriptional activation (C-terminal domain phosphorylation) (Fig.…”
Section: Cdk8 and Cdk19 Dissociate From C/ebp␤ Target Gene Promoters mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported the novel observation that cardiac Med13 functions to regulate whole-body energy homeostasis (22,23) and that Med1 is essential in postnatal and adult cardiomyocytes (24); however, the function of Mediator kinase activity has yet to be determined. Knockdown and overexpression studies in other systems have shown that Cdk8 can impart both activating and repressive effects on transcription in celland gene-specific contexts (25)(26)(27)(28). Cdk8 is a proline-directed serine/threonine kinase similar to MAPKs and other Cdks and is able to phosphorylate and regulate chromatin-localized proteins (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…We have now generated a class of noncytotoxic small molecules that inhibit p21-induced transcription and that were identified as selective inhibitors of CDK8 and its isoform CDK19 (21,22). CDK8 is an oncogenic CDK family member that plays no role in cell-cycle progression but regulates several transcriptional programs involved in carcinogenesis (23) and the stem-cell phenotype (24).…”
mentioning
confidence: 99%